Carbon-Ion beam radiosensitivity study and biological responses of high-yieldingrice line, MR219-PL-5 - Asrapil Waitul Fifika; Asmuni Mohd Ikmal; Ahmad Faiz; Nor’aishah Hasan; Harun Abdul Rahim; Hussein Sobri; Noraziyah Abd Aziz Shamsudin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The carbon ion-beam has emerged as a novel physical mutagen for creating genetic variability and crop improvement. In this study, seeds of a high-yielding pyramided rice line MR219-PL-5 were exposed to carbon ion beam irradiation at 10, 20, 40, 60, 80, and 100 Gy. The radiosensitivity test was conducted to determine the optimum dose of carbon ion beam irradiation based on the lethal dose 50% (LD50) using Sandwich Blotter Technique. The biological responses of carbon-ion beam irradiation were also observed in other characteristics such as germination rate (GeR), survival rate (SR), growth rate (GRoR), shoot length (SL), root length (RL), seedling height (SH), days to flowering (DTF), fertility rate (FR) and thousand-grains weight (TGW). Based on the polynomial curve of SR graph, the lethal dose 50% (LD50) value was 86.12 Gy. However, the optimum dose range of carbon ion-beam irradiation was between 40 and 60 Gy as these two doses recorded the highest SR, 63 and 67%, respectively. Furthermore, the shoulder dose in this study was 60 Gy since SR decreased significantly at higher doses. M1 individuals irradiated at 40 and 60 Gy had the best biological responses where significant differences were found for SR, SL, RL, GRoR, SH, DTF and FR at these two doses compared to the other doses. Further studies on M2 and M3 populations could help to identify potential individuals as well as to understand the inheritance of each trait of interest from one generation to the next.